Women ’ s Experiences of Sexual Pleasure in Ghana - Fiaveh, D.Y.; Okyerefo, M.P.K.; Fayorsey, C.K. (Springer Science+Business Media New York, 2015)
Abstract Although sexual intercourse is an important aspect of women’s sexuality, there is little knowledge on how women experience sexual pleasure in Ghana. In this paper we explore how women and men express sexual pleasure and highlight women’s experience of sexual pleasure based on the narratives of 20 women and 16 men. Specifically, we focus on describing how women and men understand sexual pleasure, the factors that stimulate sexual pleasure, and show how women experience it. The interviewee’s expressions of sexual pleasure were symbolic and had both direct and indirect manifestation. Ejaculation was reported to indicate a direct manifestation of sexual pleasure. Screams, facial and other expressions were reported to indicate indirect experiences of sexual pleasure, and were seen to be associated with female sexuality more than male sexuality. Women and men expressed sexual pleasure in a variety of ways (e.g., ejaculation, screaming, “good pain”, treating a partner nicely after sex, asking rhetoric questions during sex, and prolonged sex intercourse) and there were no differences in the meanings both women and men ascribed to sexual pleasure, regardless of their demographic profiles. Women reported experiencing sexual pleasure as their male partners did based on meanings they attach to erotic sensuality as expressed in romance, foreplay, and physical attractiveness. If sex is sexually stimulating (e.g., due to a partner’s agreeable personal hygiene), women would engage in it. Well-intentioned sexuality programmes emphasizing partners’ touching each other for pleasure, as well as educating partners to maintain erotic sensuality is compelling for inducing sexual pleasure.
Keywords: Sexual pleasure; Sensuality; Sexuality; Eroticism; Ghana